Estilo parental e problemas de comportamento em crianças e adolescentes em Foz do Iguaçu: determinação dos fatores associados - Camargo Junior, Ruy Bueno (2019)
The present study constitutes analytical, transversal and quantitative research, carried out at the Clinical School of Psychology of the Uniamérica University Center, Foz do Iguaçu, Paraná. The objective was to investigate behavioral problems in children and adolescents and their relationship with parental style. Parents or guardians and children or adolescents from 6 to 18 years of age were recruited, referred to Clínica Escola, and convenience sampling was used. To collect data were applied to parents or guardians: Socioeconomic / clinical questionnaire; Inventory of Behaviors for Children and Adolescents aged 6 to 18 years (CBCL / 618); Parenting Styles Inventory IEP; SelfAssessment Inventory for Adults (ASR / 1859). In the children or adolescents were applied: Inventory IEP Maternal Parenting Practices; IEP Parental Parenting Practices; SelfAssessment Questionnaire for Adolescents (YSR / 1118). The instruments were applied from july to november 2018. For the identification of possible relationships between the dependent and independent variables studied, nonparametric tests (Chisquare, Fisher's Exact Test and Spearman's Test) were used and the parametric Pearson Linear Correlation test, using the Minitab 18 program. As a result, there were 69 dyads (responsible / child) and there was a predominance of referrals to the schoolclinic due to school problems and behavior/aggression problems. However, the incidence of internalizing problems was greater than externalizing problems in children. Negative parenting practices correlated with greater occurrence of behavioral problems and lower indicators of adaptive functioning in both children and caregivers. While positive practices were associated with appropriate behaviors and improved adaptive functioning in the responsible/child dyad. There was an association between parental style of risk and externalizing problems (rule breaking and aggressive behavior), conduct disorder and oppositional disorder, somatic complaints and problems of thinking in the child / adolescent. The parental style of risk from the perspective of the child was associated with low school competence from the perspective of the person in charge. It was identified that behavioral problems in those responsible are strongly related to behavioral problems in children, while the adaptive functioning of those responsible was shown to be positively correlated with social skills in children/adolescents. We found a significant association between parental risk and low family income and the problem of internalizing behavior in parents/guardians. There was greater agreement among informants for externalizing than for internalizing problems, and there was generally agreement, albeit weak, between the report of the responsible and the selfreport of the child adolescent. The results point to a certain reliability in the evaluation made through the IEP applied in children when compared to the IEP applied in the mothers. It is concluded that the parents' educational practices, their parental styles, modulate the children's behaviors possibly through reinforcement processes that act, in most cases, in a bidirectional way. The importance of including the parents 'or guardians' evaluation, the training of more functional educational practices and the attention to the mental health of these caregivers is highlighted with the result of this study.